2012
DOI: 10.1021/nl301610z
|View full text |Cite
|
Sign up to set email alerts
|

Low-Resistivity 10 nm Diameter Magnetic Sensors

Abstract: Resistivities of 5.4 μΩ·cm were measured in 10-nm-diameter metallic wires. Low resistance is important for interconnections of the future to prevent heating, electromigration, high power consumption, and long RC time constants. To demonstrate application of these wires, Co/Cu/Co magnetic sensors were synthesized with 20-30 Ω and 19% magnetoresistance. Compared to conventional lithographically produced magnetic tunnel junction sensors, these structures offer facile fabrication and over 2 orders of magnitude low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 75 publications
0
51
0
Order By: Relevance
“…Magnetic nanoparticles have potential biological and biomedical applications, 1−6 applications in high-resolution magnetic imaging, 7−9 as magnetic sensors, 10 and as dense magnetic storage media. 11 At the same time, the low-dimensionality of these structures results in magnetic configurations not present in macroscopic magnets.…”
Section: Abstract: Magnetic Nanotubes Cantilever Magnetometry Magnementioning
confidence: 99%
“…Magnetic nanoparticles have potential biological and biomedical applications, 1−6 applications in high-resolution magnetic imaging, 7−9 as magnetic sensors, 10 and as dense magnetic storage media. 11 At the same time, the low-dimensionality of these structures results in magnetic configurations not present in macroscopic magnets.…”
Section: Abstract: Magnetic Nanotubes Cantilever Magnetometry Magnementioning
confidence: 99%
“…[41][42][43][44] Further design of parameters for potential pulse electrodeposition of CoFe nanowires in quiescent plating solutions were chosen on the basis of the CV experiment shown in Fig. 3a.…”
mentioning
confidence: 99%
“…Recent experimental and theoretical work has demonstrated that nanometer-scale magnets, as a result of their low dimensionality, display magnetic configurations not present in their macroscopic counterparts [1][2][3]. Such work is driven by both fundamental questions about nanometerscale magnetism and the potential for applying nanomagnets as elements in high-density memories [4], in high-resolution imaging [5][6][7], or as magnetic sensors [8]. Compared to nanowires, ferromagnetic nanotubes are particularly interesting for magnetization reversal as they avoid the Bloch point structure [9].…”
mentioning
confidence: 99%